Micro-site conditions significantly affect growth performance and climate signals of Scots pine at its northern distribution limits - Lange, Jelena; Buras, Allan; Garcia, Roberto Cruz; Gurskaya, Marina; Jalkanen, Risto; Seo, Jeong-Wook; Wilmking, Martin
Abstrakti At its northern distribution limits, growth of Scots pine is generally driven by summer temperature. However, some studies found a decoupling of tree growth and summer temperature in certain parts of boreal Eurasia and propose reduced water availability as a possible explanation (e.g. Wilmking et al. 2005). Moreover, Düthorn et al. (e.g. 2016) demonstrated that differing micro-site conditions influence Scots pine growth in Fennoscandia. To investigate the effect of differing micro-site conditions on a broader spatial scale, we analyzed tree-ring width (TRW) and maximum latewood density (MXD) over six sites, spanning three latitudinal gradients in Eurasia (Finland, Western and Central Russia), and included dry and wet micro-site conditions at each site. Per site and proxy we performed a Principal Component Gradient Analysis (PCGA) to explore the existence of sub-populations with different growth patterns. For each identified sub-population proxy, climate-growth relationships were calculated. At five out of six sites, PCGA showed a clear distinction between dry and wet micro-sites. Corresponding climate correlations were stronger on dry than on wet sites with more pronounced effects for TRW in comparison to MXD. Concluding, our preliminary results corroborate the assumption that Scots pine growth might be affected by micro-site conditions, which certainly has implications for dendroecological and –climatological studies. 2017